Effects of Arbuscular Mycorrhiza on Osmotic Adjustment and Photosynthetic Physiology of Maize Seedlings in Black Soils Region of Northeast China - Xu,Hongwen (2016)
ABSTRACT To investigate the effect of arbuscular mycorrhiza fungi on maize growth, osmoregulation substances and photosynthetic physiology, a popular maize variety ZD 958 was measured under potted condition. Arbuscular mycorrhiza (AM) symbiosis promoted plant growth, and enhanced plant height, leaf length, mean leaf width and dry weight. Higher soluble sugar and protein, but lower proline concentrations were detected in AM seedlings than corresponding non-AM seedlings. Quantum yield of PSII photochemistry and potential photochemical efficiency increased by arbuscular mycorrhiza fungi, meanwhile, AM plants had lower primary fluorescence but higher maximal fluorescence and variable fluorescence than non-AM plants. AM enhanced apparent quantum efficiency, maximum net photosynthetic rate, dark respiration rate and light saturation point, but reduced light compensation point. The conclusion was that, after the seedling inoculated with Glomus. tortuosum, AM symbioses could protect cell from being hurt through regulating substances related to osmotic adjustment, besides, the efficiency of light utilization, the capacity of using low light and the capacity of fitting and using high light were all increased by AM symbiosis.